2009
DOI: 10.1007/s10107-009-0305-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining and scaling descent and negative curvature directions

Abstract: The aim of this paper is the study of different approaches to combine and scale, in an efficient manner, descent information for the solution of unconstrained optimization problems. We consider the situation in which different directions are available in a given iteration, and we wish to analyze how to combine these directions in order to provide a method more efficient and robust than the standard Newton approach. In particular, we will focus on the scaling process that should be carried out before combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In order to illustrate the effect of our approach, we selected a benchmark of 61 smooth problems from the CUTEst collection [16] for which first and second-order derivatives were provided and negative curvature was detected, inspired by the benchmark of Avelino et al [2] 2 . Table 1 list the problems and their dimensions.…”
Section: Numerical Illustrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to illustrate the effect of our approach, we selected a benchmark of 61 smooth problems from the CUTEst collection [16] for which first and second-order derivatives were provided and negative curvature was detected, inspired by the benchmark of Avelino et al [2] 2 . Table 1 list the problems and their dimensions.…”
Section: Numerical Illustrationsmentioning
confidence: 99%
“…A partial explanation may be found in the theory established for second-order convergent (derivative-based) line-search methods [2,15,21,23]. In such studies, it has been identified that an algorithm exploiting both directions of descent and of negative curvature should not necessarily associate those with the same step length.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We compare implementations of Algorithms 2.1 and 3.1 on less pathological cases than the one mentioned above. The test functions are taken from the CUTEst package [24], and have been identified as presenting negative curvature at some points by Avelino et al [5,Table 6].…”
Section: Numerical Observationsmentioning
confidence: 99%
“…This represents a total of 60 problems out of the 119 problems tested in [5]. For all of those problems, we used the smallest dimension available in the SIF files, resulting in 36 problems with dimensions less than 10, 22 problems having dimensions between 10 and 15, 1 problem with dimension 28, and 1 problem with dimension 50.…”
Section: Numerical Observationsmentioning
confidence: 99%